Calcium peroxide (CaO2) granules enclosed in fabrics as an alternative H2O2 delivery system to combat Microcystis sp - Keliri, Eleni; Adamou, Panayiota; Efstathiou, Nektarios; Kokkinidou, Despoina; Kapnisis, Konstantinos; Anayiotos, Andreas; Mazur-Marzec, Hanna; Antoniou, Maria G. (My University, 2022)
Hydrogen peroxide (H2O2) is considered the most environmentally friendly method to combat toxic cyanobacterial as it selectively oxidizes them without forming harmful by-products. Recently, calcium peroxide (CaO2) granules were proposed as an alternative algaecide to liquid H2O2 for their slow H2O2 release properties. Herein, concentrations of 0.5, 1.0, and 2.0 g/L CaO2 granules were added into a surface water matrix to investigate their H2O2 releasing properties. Then, select concentrations of granules were enclosed in four types of fabric delivery systems to evaluate their overall oxidant releasing capacity. No difference was observed between the maximum H2O2 concentrations of the direct application of granules and the fabric delivery systems for types A – C, which released up to 12 mg/L H2O2 by 2.0 g/L CaO2 granules at t = 24 h. Fabric system type D had the lowest H2O2 releasing capacity. Based on the above, delivery systems A to C were further investigated for their suitability to combat cyanobacteria. To examine their efficiency on Microcystis sp., bench-scale treatments were performed in various CaO2 granules enclosed in fabrics (GEF) concentrations. GEF type B of concentration 2 g/L and type C concentrations of 1 g/L and 2 g/L were sufficient to reduce the photosynthetic activity of Microcystis species from 8000 to <1000 RFU. GEFs can be considered as a sustainable method to combat cyanobacterial blooming, since they minimize granules’ availability into the waterbody, and hence eliminate adverse impact on non-targeted species. Moreover, these delivery systems promote the circular economy by implementing practices that make use of reused and recycled fabrics.
Keywords: Calcium peroxide; Microcystis sp.; Oxidation; Fabrics; Treatment